ТHE MAIN ASPECTS OF SUSTAINABLE TOURISM DEVELOPMENT IN THE BORDER AREAS OF KAZAKHSTAN AND KYRGYZSTAN - Savanchieva Armanai Sagatbaevna; Ananchenkova Polina Igorevna; Karimbergenova Madina Kudaibergenovna; Zhaltyrova Olga Ivanovna; Kuangalieva Tursynzada Kuangalievna; Maslova Irina Alekseevna (Scientific Journal of Pedagogy and Economics, 2021)
An important factor in the development of tourism within transboundary territories may be unique tourist resources, or special areas. Border territories often turn into gambling zones, especially in those cases when the industry of gambling entertainment is prohibited in neighboring countries. In addition, a tourist product can be formed on the basis of unique tourist resources, united by a common idea or historical plot. You can get to know them only by traveling from a neighboring or nearby country. Tourists are attracted to the border space by duty-free trade, a large selection of goods, lower prices, convenient opening hours. On the basis of the Agreement, the Republic of Kazakhstan and the Kyrgyz Republic will contribute to expanding cooperation in the field of tourism in order to familiarize citizens of their states with achievements in the field of economics, social development, culture, nature and sights, as well as historical monuments and national traditions of the peoples of the three countries. The parties will cooperate in the development of international tourism on the basis of equality, mutual benefit and, in order to increase the tourist flow, facilitate the simplification of visa and customs formalities, exchange lists of travel agencies. The Parties will facilitate the exchange of experience in all areas of international and domestic tourism, promote cooperation between the national tourism administrations of the Parties and other organizations involved in tourism and its development. The parties will also facilitate the dissemination of tourist information to attract the flow of tourists through the publication of promotional materials, the exchange of information, print media, exhibitions, films and the holding of various symposia and seminars. The parties will provide mutual assistance in the training of personnel of tourist complexes and facilitate the exchange of specialists of the relevant tourism authorities, assist the relevant departments and interested organizations in the creation of joint ventures and in the implementation of other investment projects in the tourism sector. The parties through the relevant tourism authorities will exchange views on cooperation, work experience in activities in international tourism organizations.